WORKSHOP PEMBUATAN PRODUK KREATIF DAN PENGELOLAAN KEUANGAN USAHA KECIL BAGI IBU-IBU PKK - Davant Kespalias Putra; Muhammad Yudha Febriyanto; Muhammad Guntur Satrio; Nugroho Heri Pramono (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to enhance creativity and financial management skills of small businesses among PKK women through a workshop on creative product development in the form of tote bags and basic small business financial management training. The background of this activity is the limited skills of the community in transforming simple items into products with selling value and the lack of understanding of managing business finances. The methods used include counseling, hands-on practice in making hand-drawn tote bags, and interactive discussions on basic small business financial concepts. The results show that participants were able to produce creative tote bags and gain initial understanding of product pricing potential and the importance of financial management. This activity positively impacts participants’ confidence, creativity, and entrepreneurial insight, and has potential as an initial step toward developing creativity-based small businesses within PKK communities.